Penerapan Metode Certainty Factor pada Sistem Pakar Kerusakan Printer Berbasis Website - Hemifitriani Lugu; Rizal Rizal (Router : Jurnal Teknik Informatika dan Terapan, 2025)
An expert system is a computer program designed to imitate the decision-making ability of an expert in a particular field, especially in printer damage, so this requires an expert system application to diagnose printer damage to users who support it by obtaining diagnostic results using the certainty factor method, in terms of the explanation of the certainty factor which has a concept based on symptoms and diagnoses from the weight of an expert's value and the user's value, then calculated using the formula on the certainty factor, the final result is the creation of an expert system for diagnosing printer damage using the website-based certainty factor method.